Adrenocortical tumours: high CT attenuation value correlates with eosinophilia but does not discriminate lipid-poor adenomas from malignancy. Issue 12 (1st August 2013) - Pennanen, Mirkka; Raade, Merja; Louhimo, Johanna; Sane, Timo; Heiskanen, Ilkka; Arola, Johanna; Haglund, Caj
Abstract : Background: Characterisation of adrenal tumours is an important clinical problem. Unenhanced CT is the primary imaging modality to assess the nature of these lesions. Aims: To study the correlation between unenhanced CT attenuation value and the specific histopathology, as well as the proportion of lipid-poor eosinophilic cells in adrenocortical tumours. Methods: We studied retrospectively primary adrenocortical tumours that had been operated on at Helsinki University Central Hospital between 2002 and 2008. Of 171 tumours, 79 had appropriate preoperative CT scans and were included in the study. We evaluated the unenhanced CT attenuation values (Hounsfield units, HU) of these tumours and determined their histopathological diagnosis by the Weiss scoring system. We also assessed the proportion of lipid-poor eosinophilic cells for each tumour. Results: Unenhanced CT attenuation value (HU) in adrenocortical tumours correlated well with the proportion of lipid-poor eosinophilic cells (rs =0.750, p<0.001). HU and Weiss score also had a correlation (rs =0.582, p<0.001). Conclusions: Unenhanced CT attenuation value correlates well with the percentage of lipid-poor eosinophilic cells, but unenhanced CT attenuation value fails to differentiate between benign lipid-poor adenomas and malignant adrenocortical tumours. All adrenocortical tumours with unenhanced CT attenuation value ≤10 HU are histologically benign lipid-rich tumours.